Detectores de partículas sobre variedades no Minkowskianas - Tejeiro, J. M. (MOMENTO, 1993)
The concepts of particle and vacuum are discussed using differents detector's models and are compared with those that arise from the second quantization method on a non-Minkowskian manifold.